POLITENESS ON INDONESIAN CULTURE PERSPECTIVE AMONG STUDENTS OF FACULTY OF LANGUAGE EDUCATION OF UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Nurul Hidayah Istiqomah (PBI 15 UMY 062, 2015)
*62 This research is a study about students’ politeness in Faculty of Language Education batch 2012. The research method was quantitative and qualitative method or usually known as mix method. The quantitative data were collected by using questionnaire, which was made to measure the students’ politeness. The qualitative data were obtained from interview. The population of the subject was 161 students. However, this research only involved 33 students. the questionnaire was distributed to 30 students, and 3 of them were interviewed. All participants were taken based on convenience sampling. The result of the research on students’ politeness was shown by the average score of Likert scale. Good level was obtained on student politeness toward parents with the average score 3.8. Then, the politeness toward teachers/lecturers had the average score 3.6. The politeness toward older people also got on average score of 3.6, while the politeness toward younger people was 3.3. The result of students’ politeness toward friends was good with the average score of 3.6. The students had also applied the manner of conversation on their daily activities with score of 3.7. In the same way, students in Faculty of Language and Education also had a good manner on clothing with score of 4.0. In summary, the students of Faculty of Language Education in UniversitasMuhammadiyah Yogyakarta had a good level of politeness as shown by the average of the mean score of 3.6